KAJIAN SISTEMATIS PENGEMBANGAN METODE PENYARINGAN SINYAL PHOTOPLETHYSMOGRAM DARI ARTIFAK GERAK DALAM AKTIVITAS OLAHRAGA - Pranandityo Bagus Suprapto, B
The importance of Heart Rate as vital sign reflecting one’s fitness and health conditions has been established since long, as well as their relation to the workload during activity such as physical exercise, and devices enabling continuous Heart Rate monitoring have been developed, such as the Electrocardiogram (ECG), which provides accurate reading of the heart’s activity through electrical reading from the chest. Unfortunately, this is at cost of user’s comfort and practical usage, which may not be suitable during physical exercise.Photoplethysmograph (often abbreviated as PPG) is the other device commonly used to measure Heart Rate, working by the optical concept of light absorption. Although it became a very practical device with relatively low cost and little usage obtrusiveness, it is vulnerable to motion artifacts during activities such as physical exercise where continuous heart rate monitoring would have proven to be beneficial. As such, efforts are made in order to minimize its effects, particularly through processing the signal using carefully designed methods consisting of various classes of algorithms such as adaptive filters, heuristic peak detection and tracking, spectral analysis, and so on. In the purpose of investigating whether the current signal processing methods could be applied to PPG devices during physical activities, this thesis attempts to review the algorithms developed by various researchers in their goal of cleansing the PPG signals from measurement noise, particularly during physical exercise where motion artifacts are at the strongest. 32 research papers searched from PubMed and IEEE Xplore detailing such algorithms were included, and its results were arranged in a table, along with details to be noted of. We conclude from the results that some of the developed algorithms could be applied for PPG signal cleansing from motion artifact with its accuracy and computational speed, but the limited samples used to evaluate them may warrant future investigation with other ethnics for cross-validation, and that future developments need to consider its applicability in terms of tunable parameters.